U.S. Media Enjoyment without Strong Media Literacy Undermines Adolescents' and Mothers' Reported Efforts to Reduce Unhealthy Eating in Jamaica. (5th August 2020) - Ferguson, Gail M.; Nelson, Michelle R.; Fiese, Barbara H.; Meeks Gardner, Julie M.; Koester, Brenda
Abstract : We investigate whether media literacy and media use can moderate the association between U.S. media enjoyment and unhealthy eating among remotely acculturating "Americanized" adolescents and their mothers in Jamaica ( n  = 164 individuals/82 dyads; M adolescent.age  = 12.83, SD  = 0.48, 48% female; M mother_age  = 39.25, SD  = 5.71). Socioeconomically diverse participants completed questionnaires reporting their degree of enjoyment of U.S. media (i.e., remote acculturation), media literacy (i.e., critical thinking about food media/advertising), and adherence to national dietary guidelines to reduce sugar/fat. Multilevel modeling showed that enjoying U.S. media and consuming high levels of U.S. TV plus Jamaican TV are associated with lower efforts to reduce sugar and fat. However, high media literacy, whether one's own or a close family member's, weakens or nullifies that association.